Spirulina platensis Geitler sebagai Fikoremediator Logam Berat Pb Skala Laboratorium - Prambodo, Muhammad Sindhunata; Hariyati, Riche; Soeprobowati, Tri Retnaningsih (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Industrial waste contributes the heavy metals pollution in the environment, especially in the water. One of the heavy metals that pollute the environment is lead (Pb). Lead is a substance that is harmful to organisms, especially humans, both adults and children. Solutions to tackle Pb pollution isby remediation process. Physical and chemical remediation methods usually costly and ineffective. One of the alternative methods which is used is the bioremediation uses microalgae or called as phycoremediation. One of microalgae which is used as agents of phycoremediation is Spirulina platensis Geitler because it’s easily cultured and it’s abundant in nature. This study aims to assess the population growth and the percentage reduction of Pb after inoculated with the use of Spirulina platensis Geitler. The method which is to cultivate S. platensis Geitler in brackish watermedia with a salinity of 15 ppt which have been added Pb with a concentration of 1 mg, 3 mg, and 5 mg for 8 days and observed the population and the percentage reduction of Pb heavy metals. Environmental factors such as temperature, salinity, pH, light intensity are conditioned to remain stable. After 8 days of research, study was able to reduce Pb. Each treatment has different concentrations decrease. Treatment Pb 1 mg of 0.949 into 0.603 mg / L; Pb 3 mg of 2.894 to 2.46 mg / L; and Pb 5 mg of 4.88 to 4.31 mg / L, with each percentage decline of 36%, 15% and 12%. The Pb 3 mg treatment has higher cell population (129.367 cell / ml) than control (106.600 cell/ml) while 1 mg and 5 mg treatment has 93.700 cell / ml and 93.500 cell / ml. Keywords: Spirulina platensis, phycoremediation, waste, lead.